Application of Stokes’ higher order theory and JONSWAP spectrum in modelling extreme wave events validation with historical data - Khan Muhammad Azeem; Nizamani Zafarullah; Nakayama Akihiko; Ahmed Mirza Munir (E3S Web of Conferences)
Accurately modelling wave elevations is critical for the design and safety of offshore structures. This study explores the application of Stokes’ 5th Order Wave Theory and JONSWAP (Joint North Sea Wave Project) spectrum to simulate wave conditions similar to those experienced during the Draugen Ringing Event. Hindcasting on the dataset collected form Norwegian Meteorological Institute sensor system Draugen is performed. Through rigorous analysis performed by integrating these models, we aim to validate their accuracy and reliability against empirical data. The methodology includes generating the JONSWAP spectrum based on significant wave heights and peak periods, followed by computing wave surface elevations using Stokes’ 5th Order Wave Theory and spectral analysis. The outcome of the analysis shows a strong correlation between the modelled irregular wave elevations and actual wave data, demonstrating the effectiveness of these models.